Hybrid-structured onion scheme against replay attack of MIX - SHI Jin-qiao; FANG Bin-xing; GUO Li; WANG Li-hong (Tongxin xuebao)
Replay attack against MIX was studied and a hybrid-structured onion scheme of MIX against replay attack was proposed.In hybrid scheme, probabilistic encryption and semantic security of universal re-encryption were utilized to protect MIX against replay attack, and the authentication property of layered encryption was utilized to protect integrity of messages.Meanwhile, symmetric encryption was imported to improve efficiency.Analysis shows that the hybrid-structured onion scheme can resist replay attack with guarantee of security and efficiency.